Learning Supervision Strategy at SDN 1 Banawa, Donggala Regency in the Review of Islamic Education Management - Hamdi Rudji (Universitas Muhammadiyah Palu, 2023)
The main problem in this study is the learning supervision strategy at SDN 1 Banawa Kab. Donggala and what is the review of Islamic education management regarding the learning supervision strategy at SDN 1 Banawa Kab. Donggala. The purpose of this study was to determine the learning supervision strategy at SDN 1 Banawa Kab. Donggala and to find out the management review of Islamic education regarding the learning supervision strategy at SDN 1 Banawa Kab. Donggala. The approach that the author uses in studying the title is qualitative by using a case study type of research at SDN 1 Banawa Kab. Donggala. The results showed that the learning supervision strategy at SDN 1 Banawa Kab. Donggala is the preparation of the supervision program, the implementation of the supervision program, the evaluation of the supervision program, the reporting of the supervision program, the follow-up of the supervision, and the development of supervision. An overview of Islamic education management on learning supervision strategies at SDN 1 Banawa Kab. Donggala is in accordance with Islamic education management because of the implementation of the supervision strategy at SDN 1 Banawa Kab. Donggala has used planning, organizing, actualizing, and controlling optimally based on local wisdom. The suggestion for this research is to carry out periodic supervision by educating, not dismissing. Furthermore, that SDN 1 Banawa is managed properly so that it is more trusted by the community and government.